Burden of chronic kidney disease in Peru: a population-based study. (March 2015) - Francis, E R; Kuo, C; Bernabe-Ortiz, A; Nessel, L; Gilman, R; Checkley, W; Miranda, J; Feldman, H; the CRONICAS Cohort Study Group,
Abstract: Background: Chronic kidney disease's (CKD) silent progression, association with other chronic diseases, and high treatment costs make it a global public health concern, especially in low-income and middle-income countries (LMIC) where health-care resources are constrained. Understanding CKD epidemiology in these countries is key to addressing CKD burden and will guide disease surveillance, screening, prevention, and resource allocation. In keeping, this study serves as one of the early descriptions of the CKD burden in Peru. Methods: In this cross-sectional study, we collected baseline demographic data and biological samples to measure markers for CKD, serum creatinine, and urine protein, from 404 participants who were a random subsample of the ongoing CRONICAS cohort study in Lima and Tumbes, Peru. Participants were identified via a single-stage sampling method and stratified by sex and age (35–44; 45–54; 55–64; and ≥65 years). Inclusion required full-time residence in the area, the ability to understand study procedures, and informed consent. Selection of participants continued until age and sex strata were filled. Trained fieldworkers went door-to-door to enrol selected participants and receive written informed consent. We used Poisson regression to identify possible factors associated with CKD. CKD was defined as estimated glomerular filtration rate (eGFR) <60mL/min/1·73m 2 or proteinuria (protein-creatinine ratio) ≥150 mg/g creatinine, or both, based on the latest Kidney Disease Improving Global Outcomes (KDIGO) guideline. Findings: Participants' median age was 54·8 years (IQR 44·9–64·8). Of the 404 participants, 68 (16·8%) met the study's CKD criteria: 60 (14·9%) with proteinuria, four (1%) with eGFR <60mL/min/1·73m 2, and four (1%) with both. CKD prevalence was higher in Lima than Tumbes (20·7% vs 12·9%, p=0·04). Among participants with CKD, the prevalence of diabetes and hypertension was 19·1% (n= 13) and 42·7% (29), respectively. After multivariable adjustment, CKD was associated with older age, female sex, the highest wealth tertile (although all wealth strata were below the poverty line), living in Lima, diabetes, and hypertension. Interpretation: This study has identified a high prevalence of CKD in our Lima and Tumbes sample groups. Our findings highlight the burden of CKD, much of which is likely occult, and suggest that expanded strategies to measure actual CKD burden through nationwide surveillance efforts are needed. In light of the few therapeutic options to slow CKD progression and low rates of access to health care and insurance in Peru, such expanded surveillance strategies may identify more disease and, therefore, help to prevent disease progression and secondary morbidity. Funding: The CKD study was funded by University of Pennsylvania. The CRONICAS Cohort Study was supported by theNational Heart, Lung, and Blood Institute (project number 268200900033C-1-0-1 ). ERF was supported by WCMC and JHBSPH.